Organizações políticas internacionais: os desafios da cooperação internacional: Breve estudo sobre dez organizações internacionais - Arena, Maria do Céu de Pinho Ferreira Pinto (2023)
International organisations (IOs) are central actors in the international system, as they are forums where ideas circulate, develop and acquire legitimacy. In this sense, they represent an important mechanism in the diffusion of conceptions on the most diverse themes, contributing to the expansion of the international agenda and even promoting the redefinition of perceptions and patterns of behaviour. They make a significant contribution to delimiting the parameters within which international relations take place. IOs have built the framework of regimes that confer some order on the international system, expanding the scope and content of international law and, in a sense, ensuring that it is respected. They indicate the appropriate means for solving the most varied international problems and provide their members with occasions to come together, to find collective solutions to problems, either at the legal level (with the drafting of agreements, treaties, regulations and the codification of international law) or at the operational level, with the provision of mediation, peacekeeping operations, humanitarian actions or measures to contain terrorism. However, IOs have some disadvantages: the form their authority takes can be tenuous and is decentralised compared to that of states; the absence of a robust common culture or the impossibility of enforcing decisions coercively. This book aims to provide an overview of the main existing international political organisations. This book focuses on the most important and representative international organisations. It presents a brief study of the UN, the Council of Europe, NATO, the Organization on Security and Cooperation in Europe (OSCE), the Community of Portuguese Speaking Countries (CPLP), the African Union, the Organization of American States, the Arab League, the Association of Southeast Asian Nations (ASEAN) and the Shanghai Cooperation Organization. The organisations will be analysed taking into account their historical genesis and the context of their creation, their organic structure, the main areas of action and a review of their activity.